Epidermal Inclusion Cyst following Percutaneous Trigger Finger Release - Tsai, Ting-Chien; Lo, Sheng-Pin; Lien, Fang-Chieh (Journal of Hand and Microsurgery, 2018)
Epidermal inclusion cyst is a benign lesion that commonly occurs due to inclusion of epidermal cells into the dermal or deeper layers in a trauma event. Percutaneous release is a minimally invasive technique, and good surgical outcomes can be achieved. However, the percutaneous procedure is a puncture injury, and the epidermal inclusion cyst is reasonable to become a possible complication. In this article, we presented a case of trigger finger in left middle finger. The patient underwent percutaneous release as the treatment and a second percutaneous release 5 months later due to recurrence of the symptoms. An epidermal inclusion cyst was noted 5 months thereafter, and it was treated with excision. With this case, we need to be more aware of this possibility if a mass lesion without infection signs occurs in the released area and recommend sonography if there is a mass lesion a few months after the procedure.
Keywords: complication; epidermal inclusion cyst; percutaneous; release; trigger finger